Hablemos por igual: el humor como propuesta para desarrollar microprogramas que combatan la violencia de género - Coloma Montoya, Gabriela Alejandra (2023)
This audiovisual project seeks to make a series of videos that, from humor, the gender perspective and feminism, will make violence against women visible in a country that has normalized sexist and discriminatory behavior towards this population group. At the same time, the initiative aims to show the absurdity of sexist practices without falling into the trivialization or re-victimization of those women who suffer from it. Likewise, from re-education and dialogue, the first chapter of “Hablemos por igual” seeks to explain the “Iceberg of Gender Violence”, which is defined as the different violent behaviors: visible or less visible. Thus, the purpose of this project is for more young people to know the importance of detecting violence in all its types, in order to guarantee the correct development of women in our society.